Multilingual development - Siemund, Peter (Cambridge University Press, 2023)
English as a global lingua franca interacts with other languages across a wide range of multilingual contexts. Combining insights from linguistics, education studies, and psychology, this book addresses the role of English within the current linguistic dynamics of globalization. It takes Singapore, Hong Kong, and Dubai as case studies to illustrate the use of English in different multilingual urban areas, arguing that these are places where competing historical assessments, and ideological conceptions of monolingualism and multilingualism, are being acted out most forcefully. It critically appraises the controversial concept of multilingual advantages, and studies multilingual cross-linguistic influence in relation to learning English in bilingual heritage contexts. It also scrutinises multilingual language policies in their impact on attitudes, identities, and investment into languages. Engaging and accessible, it is essential reading for academic researchers and advanced students of bi- and multilingualism, globalization, linguistic diversity, World Englishes, sociolinguistics, and second/third language acquisition.
10.1017/9781108915540
Keywords: Multilingualism; English language